Case-control study of platelet glycoprotein receptor Ib and IIb/IIIa expression in patients with acute and chronic cerebrovascular disease. - Peter Kraft; Christiane Drechsler; Ignaz Gunreben; Peter Ulrich Heuschmann; Christoph Kleinschnitz (PLoS ONE, 2015)
Animal models have been instrumental in defining thrombus formation, including the role of platelet surface glycoprotein (GP) receptors, in acute ischemic stroke (AIS). However, the involvement of GP receptors in human ischemic stroke pathophysiology and their utility as biomarkers for ischemic stroke risk and severity requires elucidation.To determine whether platelet GPIb and GPIIb/IIIa receptors are differentially expressed in patients with AIS and chronic cerebrovascular disease (CCD) compared with healthy volunteers (HV) and to identify predictors of GPIb and GPIIb/IIIa expression.This was a case-control study of 116 patients with AIS or transient ischemic attack (TIA), 117 patients with CCD, and 104 HV who were enrolled at our University hospital from 2010 to 2013. Blood sampling was performed once in the CCD and HV groups, and at several time points in patients with AIS or TIA. Linear regression and analysis of variance were used to analyze correlations between platelet GPIb and GPIIb/IIIa receptor numbers and demographic and clinical parameters.GPIb and GPIIb/IIIa receptor numbers did not significantly differ between the AIS, CCD, and HV groups. GPIb receptor expression level correlated significantly with the magnitude of GPIIb/IIIa receptor expression and the neutrophil count. In contrast, GPIIb/IIIa receptor numbers were not associated with peripheral immune-cell sub-population counts. C-reactive protein was an independent predictor of GPIIb/IIIa (not GPIb) receptor numbers.Platelet GPIb and GPIIb/IIIa receptor numbers did not distinguish between patient or control groups in this study, negating their potential use as a biomarker for predicting stroke risk.